The Influence Of Interpersonal Communication And Management Conflicts On Employee Performance With Transformational Leadership As Intervening Variables In The Office Sidikalang District Dairi Regency - Dameika Tambunan; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the effect of interpersonal communication and conflict management on employee performance with transformational leadership as an intervening variable at the Sidikalang District Office, Dairi Regency. The research method used is quantitative associative casual with data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Data were obtained from questionnaires distributed to 49 employees and analyzed using SmartPLS 3.0 software. The results showed that interpersonal communication has a positive and significant effect on employee performance with a T-Statistic value of 6.805 (> 1.96) and a P-Value of 0.000 (< 0.05). Conversely, conflict management does not have a significant effect on employee performance with a T-Statistic value of 0.562 (< 1.96) and a P-Value of 0.577 (> 0.05). Transformational leadership has a positive and significant effect on employee performance with a T-Statistic value of 6.271 (> 1.96) and a P-Value of 0.000 (< 0.05). This study confirms the importance of interpersonal communication and transformational leadership in improving employee performance optimally.